Behavioral Changes in Cats Following Deslorelin Implantation or Surgical Gonadectomy - Mihaela Velkovska; Maria Pereira; Maja Zakošek Pipan; Darja Pavlin; Lluis Ferré-Dolcet; Simona Normando; Stefano Romagnoli (Veterinary Sciences)
Few studies address behavioral changes after deslorelin treatment in cats. As increasingly more owners opt for pharmacological sterilization, understanding deslorelin effects on behavior is critical. This multicentric study compared behavioral changes in cats that were surgically sterilized with those that were treated with deslorelin using an anonymous survey of 19 behavioral changes. Owners of deslorelin-implanted cats completed two questionnaires related to the flare-up and downregulation periods, while owners of gonadectomized cats completed only one questionnaire. A total of 66 answers were collected (24 for surgical sterilization, 24 for flare-up, and 18 for downregulation). Decrease in urine marking, excessive vocalization, intact male cat urine odor, and disobedience were significantly higher in downregulated cats compared to gonadectomized ones. In the flare-up group, 68% of females exhibited behavioral manifestation of induced heat. Males displayed flare-up behaviors less frequently and intensively than females after implantation with deslorelin. Age at sterilization exerted a significant effect on five behaviors in deslorelin-implanted cats. Owners of deslorelin treated cats in the downregulation phase reported a more pronounced decrease in undesirable behaviors than the owners of surgically sterilized cats.